(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2020)
The paper discusses the process of formation and development of non-governmental international organizations operating in the field of elections. The classification of these organizations by levels and areas of activity is proposed. The main focus of these types of actors is election observation. The role of Russia in the development of international non-governmental organizations in the field of elections is revealed. The part of particular leading actors, primarily the Global Network of National Election Observers, is defined. The conclusion was reached that the connection of these organizations with certain countries is weakening, while their support from other international actors is increasing. It is determined that at the present stage, non-governmental organizations can influence the organization of the electoral process, bypassing the national level of government and having a direct impact on international structures